2022
DOI: 10.1186/s12979-022-00265-0
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity C-reactive protein and glycated hemoglobin levels as dominant predictors of all-cause dementia: a nationwide population-based cohort study

Abstract: Background Chronic inflammation might play a major role in the pathogenesis linking diabetes mellitus (DM) to cognition. In addition, DM might be the main driver of dementia risk. The purpose of the present study was to evaluate whether inflammation, glycation, or both are associated with the risk of developing all-cause dementia (ACD). Methods A nationwide population-based cohort study was conducted with 4113 participants. The data were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… 38 Another population‐based cohort study found that the highest tertile of hs‐CRP (examined only as a categorical variable) was associated with all‐cause dementia at 8 years follow‐up. 39 The relationship was only significant in the subgroup of participants age < 65 years old. 39 This difference related to age was reported in another study specifically looking a diagnosis of AD ( n = 52).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“… 38 Another population‐based cohort study found that the highest tertile of hs‐CRP (examined only as a categorical variable) was associated with all‐cause dementia at 8 years follow‐up. 39 The relationship was only significant in the subgroup of participants age < 65 years old. 39 This difference related to age was reported in another study specifically looking a diagnosis of AD ( n = 52).…”
Section: Discussionmentioning
confidence: 93%
“… 39 The relationship was only significant in the subgroup of participants age < 65 years old. 39 This difference related to age was reported in another study specifically looking a diagnosis of AD ( n = 52). 40 There was however no association between hs‐CRP and AD in the overall group, and no cognitive testing was performed as part of the study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is well-established that combination of hyperglycemia and chronic inflammation is associated with early subclinical carotid atherosclerosis progression and increased risk of new vascular events in diabetic as well as nondiabetic subjects [ 33 , 34 ]. The existing recognized biomarkers hemoglobin A1c (HbA1c) and Hs-CRP are the most clinically useful surrogates for identifying the presence of both insulin resistance and inflammation in T2DM [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36] Some research has shown that non-Hispanic Black women have the highest levels of CRP in comparison to non-Hispanic White women and men, and even non-Hispanic Black men. [37][38][39] Circulating levels of CRP have been associated with higher white matter hyperintensity, 40 Alzheimer's disease, 35 and all-cause dementia, 41 albeit in studies of homogeneous populations that differ from the racial demographic composition of the United States. In a racially diverse population-based study in the United States, elevated serum levels of CRP were associated with two cognitive domains (memory and verbal fluency) at baseline; but not with the rate of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%